Sovereign Stress, Banking Stress, and Corporate Financing Costs in the Euro Area - Oliver Holtemöller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, we employ firm-level data to analyze to what extent financing conditions of non-financial corporations in the Euro Area depend on country-specific factors, in particular the respective country's government bond yield and the share of non-performing loans to the corporate sector. Moreover, we assess whether this relationship has changed during the European debt crisis. It turns out that the increase in corporate financing costs during the year 2011 can partially be explained by increasing government bond yields. However, the further increase of corporate financing costs in stressed Euro area countries during the year 2012 can not be explained by these yields, but by the share of non-performing loans. This finding suggests that the ECB's policy of reducing corporate financing costs in stressed countries via government bond purchases may not be effective.
Keywords: E43; E44; E52; 330